Development of a computerized visual feedback system to re-educate functional pinch in patients with motor or sensory deficits - Ferland, G.; Torres-Moreno, R. (1996 15th Southern Biomedical Engineering Conference, 1996)
Precision grip, such as lateral pinching, is an essential component of independent hand function. This apparently simple motor task, relies on a complex interaction of sensory and motor mechanisms. Patients with impaired input from proprioceptors and cutaneous receptors may experience difficulty with timing and scaling motor recruitment during manipulative manoeuvres. To help evaluate and retrain motor control of the hand, an instrumented pinching device with a computerized on-line visual feedback system responding to pinch force variation was designed and constructed. Mechanical testing of the device included step loading, loading-unloading cycles and 4 hours of constant loading to evaluate hysteresis, nonlinearity and signal shift over time. Calibration coefficients were calculated in the active range of 0 to 100 Newtons. A pilot test was then conducted using normal subjects (n=6). The experimental session for each subject consisted of a total of 30 trials: one trial per pinch span (12.3, 31.4 and 51.7 mm) to determine the maximal force (MF), and three repeated measures per force target (FT) level (25, 50 and 75 per cent of MF) per span. Data was filtered (Fc=10 Hz) and then normalized in terms of Ff level. Overall, subjects achieved better pinch force control at lower FT levels and at the thickest span tested. This study provided the basis for a clinical pilot test to determine the effectiveness of this rehabilitation tool in re-educating functional pinch in patients with sensorimotor impairments.